Sleep Apnea and Risk of Influenza-Associated Severe Acute Respiratory Infection: Real-World Evidence - Tsai MS; Chen HC; Li HY; Tsai YT; Yang YH; Liu CY; Lee YC; Hsu CM; Lee LA (Nature and Science of Sleep, 2022)
Ming-Shao Tsai,1– 4,* Hung-Chin Chen,1,* Hsueh-Yu Li,2,5 Yao-Te Tsai,1,2 Yao-Hsu Yang,4,6,7 Chia-Yen Liu,4 Yi‑Chan Lee,2,8 Cheng-Ming Hsu,1,2 Li-Ang Lee2,5,9 1Department of Otolaryngology – Head and Neck Surgery, Chiayi Chang Gung Memorial Hospital, Chiayi, 613, Taiwan; 2Faculty of Medicine, College of Medicine, Chang Gung University, Taoyuan, 333, Taiwan; 3Graduate Institute of Clinical Medical Sciences, College of Medicine, Chang Gung University, Taoyuan, 333, Taiwan; 4Health Information and Epidemiology Laboratory of Chang Gung Memorial Hospital, Chiayi, 613, Taiwan; 5Department of Otolaryngology – Head and Neck Surgery, Linkou Chang Gung Memorial Hospital, Taoyuan, 333, Taiwan; 6Department of Traditional Chinese Medicine, Chiayi Chang Gung Memorial Hospital, Chiayi, 613, Taiwan; 7School of Traditional Chinese Medicine, College of Medicine, Chang Gung University, Taoyuan, 333, Taiwan; 8Department of Otolaryngology – Head and Neck Surgery, Keelung Chang Gung Memorial Hospital, Keelung, 204, Taiwan; 9School of Medicine, National Tsing Hua University, Hsinchu, 300, Taiwan*These authors contributed equally to this workCorrespondence: Li-Ang Lee, Department of Otolaryngology – Head and Neck Surgery, Linkou Chang Gung Memorial Hospital, No. 5, Fu-Hsing Street, Gueishan District, Taoyuan City, 33305, Taiwan, Tel +886 3 3281200 ext. 3968, Fax +886 3 3979361, Email 5738@cgmh.org.twPurpose: We executed the presented retrospective cohort study with the purpose of probing the risk of severe acute respiratory infection (SARI) following influenza in patients with sleep apnea.Materials and Methods: We executed this real-world study by gathering Taiwan National Health Insurance Research Database (NHIRD) data. From a database containing 1 million individuals sampled at random from the NHIRD, we identified all patients aged 20 years or older with a sleep apnea diagnosis between 1997 and 2013 as the study group. We established a comparison cohort of individuals without sleep apnea by randomly matching patients with respect to monthly income, gender, urbanization level, and age at a 1:4 ratio. Follow-up was performed until death or the end of 2015 for both groups. We determined the study outcome to be the occurrence of influenza-associated SARI.Results: We enrolled 6508 and 26,032 patients into the study and comparison groups, respectively. A significantly higher cumulative incidence of influenza-associated SARI was discovered in the study group (p < 0.001). In our multivariate analysis, sleep apnea, chronic obstructive pulmonary disease, and coronary artery disease were independent risk factors for influenza-associated SARI. The hazard ratio of sleep apnea for influenza-associated SARI was 1.98 (95% CI: 1.26– 3.10) after adjustment for all comorbidities, gender, age, monthly income, and urbanization level.Conclusion: Sleep apnea increased the risk of influenza-associated SARI. We suggest that physicians be cautious about the development of severe influenza illness in patients with sleep apnea. Vaccination and early oseltamivir administration should be actively considered in this group of patients.Keywords: sleep apnea, sleep disturbance, influenza, severe acute respiratory infection